2004
DOI: 10.18512/1980-6477/rbms.v3n1p10-20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extrusion on Essential Amino Acids Profile and Color of Whole-Grain Flours of Quality Protein Maize (qpm) and Normal Maize Cultivars

Abstract: Whole-grain flours of Quality Protein Maize (QPM) and normal maize were extruded under controlled conditions in order to evaluate the effect of extrusion on the essential amino acids profile and color of the raw material used in the production of maize based extrudates. Flours were conditioned to 150g/kg moisture and processed in a single screw extruder at a screw compression ratio of 3:1, screw speed of 80 rpm, and die head temperature of 130 0 C, using two different die nozzle diameters (3 and 5 mm). Extrusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…African tall extrudates showed an increase, whereas HQPM1 and waxy extrudates showed a decrease in a * with rise in ET. This may attributed to the white color of African tall where the nonenzymatic browning caused an increase in redness (Paes and Maga, ). HQPM1 extrudates from each RS showed a significant decrease in b * value with rise in ET which might be attributed to the partial destruction of certain pigments imparting yellow color to HQPM1 (Paes and Maga ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…African tall extrudates showed an increase, whereas HQPM1 and waxy extrudates showed a decrease in a * with rise in ET. This may attributed to the white color of African tall where the nonenzymatic browning caused an increase in redness (Paes and Maga, ). HQPM1 extrudates from each RS showed a significant decrease in b * value with rise in ET which might be attributed to the partial destruction of certain pigments imparting yellow color to HQPM1 (Paes and Maga ).…”
Section: Resultsmentioning
confidence: 99%
“…This may attributed to the white color of African tall where the nonenzymatic browning caused an increase in redness (Paes and Maga, 2004). HQPM1 extrudates from each RS showed a significant decrease in b * value with rise in ET which might be attributed to the partial destruction of certain pigments imparting yellow color to HQPM1 (Paes and Maga 2004). African tall and waxy extrudates showed a small change in b * with rise in ET.…”
Section: Fried Extrudatesmentioning
confidence: 96%
See 1 more Smart Citation
“…S2a), it was observed that with increased screw speed, the lightness of extrudates increased significantly, although lightness was increased initially in accordance with increase in barrel temperature but declined slightly at higher temperature. The fading was attributed to the partial destruction of pigments upon processing, resulting in extrudates with higher L‐values (Paes & Maga, ); however, L* value decreased on further increase in temperature as higher temperatures are known to promote nonenzymatic browning. Increase in screw speed resulted in increase in brightness due to low retention time in extruder (Nazir et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…The higher L* value indicated greater lightness of extrudates. As more expanded extrudates had higher surface area that caused light to disperse, giving a lighter appearance to the puffed products (Paes and Maga 2004). The interaction effect of SS and ET on L* value was significant.…”
Section: Color Propertiesmentioning
confidence: 90%